Redox behavior of a low-doped Pr-CeO2(111) surface. A DFT+U study - Milberg, Brian (2017)
In this work, we investigated the redox behavior (donation and replenishing of oxygen) of a low praseodymium (Pr)-doped CeO2(111) surface. We considered a 3.7 at.% Pr doping and performed density functional calculations using the GGA formalism with the ‘U’ correction on Ce(4f) and Pr(4f) orbitals. Our results indicate that Pr doping promotes oxygen donation by lowering the energy necessary to form surface anionic vacancies. When the Ce0.963Pr0.037O2(111) surface donates one oxygen, the two excess electrons locate on Pr and Ce cations and reduce them to Pr3+ and Ce3+ ones. Praseodymium doping also favors the activation of O2 molecule on surface O-holes, leading to formation of a superoxide (O2−) radical as well as to reoxidation of the Ce3+ cation to Ce4+ one. Additionally, we used the CO molecular adsorption for testing the reactivity of those superoxide species. The calculations expose the ability of these radicals to oxidize CO forming a CO2 molecule floating on the surface. However, when the superoxide is in the immediate vicinity of Pr dopant a carbonate-type species is formed. Our theoretical results may help to gain insight into redox properties and improved catalytic performance of low-doped Pr-CeO2 solids.